Overall migration in take-away paper and paperboard packaging materials - Cedeño, Trisha Denise D.; Francisco, Ma. Leonora DL. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
The overall migration in take-away paper and paperboard packaging materials was studied in this research in order to determine migration of paper components in aqueous, acidic, ethanolic, and alternative fatty food simulants so as to evaluate the safety and suitability of paper and paperboards as packaging materials of different types of food products subjected under various time and temperature combinations. In this study, total immersion procedure was applied followed by gravimetric analysis. The food contact materials used in this study were the top food packaging materials being used by food vendors inside the UP Diliman campus. The results obtained show that among the three types of paper packaging materials used, sample 2 was relatively considered to be effective against migration as it was the only sample to have values which fall below the overall migration safety limit of 7.75 mg/dm2 at 1.58 mg/dm2, 7.65 mg/dm2, 2.44 mg/dm2, and 5.47 mg/dm2 in 3% acetic acid (100 C/1h), 10% ethanol (100 C/1h and 70 C/2hrs), and 95% ethanol (60 C/30m), respectively. Sample 2 was found to be similar to instant cup noodles being sold in the market, having functional barrier properties from surface coatings such as polyethylene (PE), expanded polystyrene (EPS), and polypropylene (PP) that help prevent further migration. Analysis of variance (ANOVA) suggests that migration was significantly different across all samples and conditions except for when they were subjected to distilled water for 1 hour at 100˚C. At high temperature and long-time conditions, the paper and paperboard packaging samples were deemed to be unsuitable for long contact time with food items, especially if such are acidic in nature. Therefore, it was observed that the nature of the food and the packaging material as well as the time of contact and temperature condition have a great impact on overall migration.
Submitted June 2016.
Thesis (BS Food Technology)--University of the Philippines Diliman.
Keywords: Food -- Packaging; Paper containers; Paperboard